1964
DOI: 10.1111/j.1476-5381.1964.tb01572.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Bethanidine on the Peripheral Circulation in Man

Abstract: Bethanidine has been administered intra-arterially and intravenously into normotensive subjects and its effects on the limb blood vessels, arterial blood pressure, vascular sensitivity to noradrenaline and the degree and time course of sympathetic nerve blockade have been studied. The drug caused an initial constriction of hand and forearm vessels which is attributed to release of catechol amines since it is abolished by the prior administration of phenoxybenzamine. The constriction was followed by a sustained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1965
1965
1984
1984

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…Nictitating membrane and pressor responses produced by intravenous injections of adrenaline and noradrenaline into cats increased in magnitude after administration of bethanidine, in a similar manner to the increases found after bretylium or guanethidine (Green, 1960;Boura & Green, 1962). In particular, the sensitivity of the nictitating membranes increased with the duration of drug administration to a maximum sensitivity after fully blocking amounts had been given for 14 days, an increase similar to that produced after postganglionic nerve section.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Nictitating membrane and pressor responses produced by intravenous injections of adrenaline and noradrenaline into cats increased in magnitude after administration of bethanidine, in a similar manner to the increases found after bretylium or guanethidine (Green, 1960;Boura & Green, 1962). In particular, the sensitivity of the nictitating membranes increased with the duration of drug administration to a maximum sensitivity after fully blocking amounts had been given for 14 days, an increase similar to that produced after postganglionic nerve section.…”
Section: Discussionsupporting
confidence: 63%
“…In this connection Laurence & Nagle (1963) found that in man single doses of bretylium and guanethidine increased the pressor response to intravenous noradrenaline without increasing vasoconstrictor responses in the forearm produced by intra-arterial injection. However, Fewings et al (1964) report an increased sensitivity to intra-arterial noradrenaline after intra-arterial infusion of bethanidine in hand blood flow experiments.…”
Section: Discussionmentioning
confidence: 90%
“…Clinical trials with bethanidine have shown that the hemodynamic effects in hypertensive patients are similar to those produced by guanethidine treatment (MONTUSCHI and PICKENS, 1962;JOHNSON et al, 1962;SMIRK, 1963;FEWINGS et al, 1964;BATH et al, 1967). PRICHARD et al (1968) did not show any significant difference between bethanidine and guanethidine in their ability to lower and control blood pressure in hypertensive patients.…”
Section: -------------------------------mentioning
confidence: 89%
“…In normal subjects the reduction in blood pressure was smaller even with suction on parts below the xiphisternum of -50 to -70 mm Hg . In these subjects regional adrenergic block of the sympathetic nerve fibres of a limb segment was obtained by an intra-arterial infusion of bethanidine sulphate (Fewings, Hodge, Scroop & Whelan, 1964) or by local intravenous administration of the drug while the circulation to the limb was occluded (Ardill, Bhatnagar & Fentem, 1967 (Sharpey-Schafer, 1963). 6.…”
Section: Methodsmentioning
confidence: 99%